Effect of sample storage conditions on the molecular assessment of MIC - Machuca Suarez, Laura; Salgar-Chaparro, S. (2018)
Microbiological surveys play a fundamental role in diagnosing and monitoring microbiologically influenced corrosion (MIC) in oil and gas production systems. Currently, microbiological characterization is being carried out by the implementation of molecular microbiological methods (MMMs) such as the 16S rRNA gene diversity profiling. Molecular characterization of microorganisms provides information to assess the risk of MIC in the production facilities. Even though MMMs have been included in NACE standards, standardized protocols for collection, storage and preservation of oilfield samples have not been written. In this study, the effect of sample storage conditions on the microbial composition, community structure, alpha diversity and functional capability of oilfield samples was investigated. The effect of storage samples at room temperature or refrigeration on the molecular MIC assessment was statistically evaluated by comparison with samples preprocessed and preserved on-site straight upon collection. Sample storage resulted in changes in the relative abundance of the microbial populations, which had a significant impact on the alpha diversity and structure of the community. Likewise, the functional capability of the microbial community in oilfield samples was affected by storage conditions. Abundances of genes associated with corrosive pathways such as sulphate reduction, iron utilization and methanogenesis decreased under conditions evaluated. Results of this research provide evidence of the importance of sample handling for an accurate microbial characterization and subsequent assessment of the MIC risk in industrial systems. Thereby, on-site pre-processing of the samples and addition of nucleic acids preservation solutions is recommended for an optimal microbiological survey, and in cases where this is not feasible, refrigeration is preferred over room temperature storage conditions.